IMPLEMENTASI PEMBELAJARAN TEMATIK TERPADU PADA KURIKULUM 2013 DI SD NEGERI WILAYAH INTI V KECAMATAN MEDANJOHOR - Nurhairani Nurhairani; Ayu Faradilla Amnaz (Universitas Negeri Medan, 2018)
Abstract: Implementation of Integrated Thematic Learning in 2013 Curriculum in Wilayah V Public Elementary School Medan Johor District. The purpose of this study was to find out how the implementation of integrated thematic learning in the 2013 curriculum in SD Negeri V SD Negeri Medan Johor District. This study is a desktiptif-qualitative study. This study is a narrative situation description (words). This research subject is a class teacher who applied integrated thematic learning in the Inti V Public Elementary School in Medan Johor District. Data collection techniques used were observation, interviews, and documentation. The results of the study showed that teachers at the Inti V Regional Elementary School in Medan Johor Subdistrict had implemented integrated thematic learning, but in its application not all teachers carry out integrated thematic learning in accordance with the characteristics of integrated thematic learning. In teacher planning has not fully developed, the teacher only uses the teacher's book in the learning process. The results of observations on the implementation of learning show that it has not been implemented as in fact, some teachers still carry out conventional learning and between subjects are still not integrated. The teacher has used authentic assessment with three aspects, namely attitudes, knowledge and skills.Keywords: Integrated Thematic Learning, Curriculum 2013Abstrak: Implementasi Pembelajaran Tematik Terpadu pada Kurikulum 2013 Di SD Negeri Wilayah Inti V Kecamatan Medan Johor. Tujuan penelitian ini untuk mengetahui bagaimana implementasi pembelajran tematik terpadu pada kurikulum 2013 di SD Negeri Wilayah Inti V Kecamatan Medan Johor.Penelitian ini merupakan penelitian kualitatif-desktiptif.Penelitian ini bersifat penggambaran keadaan secara naratif (kata-kata).Subjek Penelitian ini adalah guru kelas yang menerapkan pembelajaran tematik terpadu di SD Negeri Wilayah Inti V Kecamatan Medan Johor.Teknik pengumpulan data yang digunakan adalah observasi, wawancara, dan dokumentasi.Hasil Penelitian menunjukkan bahwa guru-guru di SD Negeri Wilayah Inti V Kecamatan Medan Johor telah melaksanakan pembelajaran tematik terpadu, namun dalam penerapannya tidak semua guru melaksakan pembelajaran tematik terpadu sesuai dengan karakteristik pembelajaran tematik terpadu. Dalam perencanaanguru belum mengembangkan sepenuhnya, guru hanya menggunakan buku guru dalam proses pembelajaran.Hasil observasi pada pelaksanaan pembelajaran menunjukkan bahwa belum terlaksana sebagaimana mestinya, beberapa guru masih melaksanakan pembelajaran secara konvesional dan antara mata pelajaran masih belum terintegrasi. Guru sudah menggunakan penilaian autentik dengan ketiga aspek yaitu sikap, pengetahuan dan keterampilan.Kata Kunci : Pembelajaran Tematik Terpadu, Kurikulum 2013